2014
DOI: 10.1186/2051-5960-2-61
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Aβ pathology and early cognitive impairments in a transgenic rat overexpressing human amyloid precursor protein: a multidimensional study

Abstract: Numerous studies have implicated the abnormal accumulation of intraneuronal amyloid-β (Aβ) as an important contributor to Alzheimer’s disease (AD) pathology, capable of triggering neuroinflammation, tau hyperphosphorylation and cognitive deficits. However, the occurrence and pathological relevance of intracellular Aβ remain a matter of controversial debate. In this study, we have used a multidimensional approach including high-magnification and super-resolution microscopy, cerebro-spinal fluid (CSF) mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
102
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 69 publications
14
102
1
Order By: Relevance
“…Only unprotected transgenic mice failed to explore the familiar but moved object any more than the other two unmoved objects (trial 2) but showed heightened exploration of the novel object (trial 3) as well as the wild type and protected transgenic mice. Thus, as in earlier and perhaps less controlled studies [61,73,[82][83][84][85][86][87][88][89][90], we also demonstrated that hippocampal degeneration decreased rodents' spatial but spared their non-spatial working memory. Even though we may have eliminated or reduced anxiety-induced behavior in NL/NOR by running mice in an enclosed maze rather than in an open field, we found in a subsequent research [91] that wild type mice could not be repeatedly tested on their NL/NOR performance.…”
Section: Transgenic Animal Models Of Adsupporting
confidence: 90%
“…Only unprotected transgenic mice failed to explore the familiar but moved object any more than the other two unmoved objects (trial 2) but showed heightened exploration of the novel object (trial 3) as well as the wild type and protected transgenic mice. Thus, as in earlier and perhaps less controlled studies [61,73,[82][83][84][85][86][87][88][89][90], we also demonstrated that hippocampal degeneration decreased rodents' spatial but spared their non-spatial working memory. Even though we may have eliminated or reduced anxiety-induced behavior in NL/NOR by running mice in an enclosed maze rather than in an open field, we found in a subsequent research [91] that wild type mice could not be repeatedly tested on their NL/NOR performance.…”
Section: Transgenic Animal Models Of Adsupporting
confidence: 90%
“…Whether toxic Aβ at synapses originates from intracellular or extracellular sources is a hotly debated topic in the field [33][34][35][36]. Here we used three high-resolution imaging techniques to examine whether oAβ is present within synaptic terminals or decorating the exterior membrane of pre and postsynapses and find that NAB61 labeled oAβ is present inside synapses.…”
Section: Discussionmentioning
confidence: 99%
“…The main issue in detecting Aβ inside cells is represented by the method used to unravel it, which is not considered sensitive enough because of the variety of staining protocols and the use of antibodies such as 6E10 and 4G8 that cross-react with APP (Aho et al, 2010). However, different methods have been used to demonstrate that Aβ is present inside neurons (for a review see Cuello et al, 2012): i) a specific antibody recognizing the N-terminal end of Aβ that does not cross-react with APP allowed to detect intraneuronal Aβ in 3×Tg and 5×FAD mice brains (Youmans et al, 2012); ii) conformation-specific antibodies have been used to detect intraneuronal Aβ in 3×Tg (Wirths and Bayer, 2012; Wirths et al, 2012); iii) a multi-dimentional study using high-resolution microscopy, mass spectrometry analysis, and ELISAs has shown that Aβ accumulates inside neurons of an AD-like transgenic rat (Iulita et al, 2014). Recently, it has been demonstrated that intraneuronal injections of Aβ caused an impairment of basal synaptic transmission and LTP.…”
Section: Aβ Between Pathology and Physiologymentioning
confidence: 99%